Post-exercise fatigue, lactate, and natural nutritional strategy - Ferrara, L.; D'Angelo, S. (Journal of Physical Education and Sport, 2023)
Exercise-induced muscle fatigue is characterized by symptoms that persist simultaneously for up to two weeks after the first workout. As a primary consequence, in the athlete manifests the reduction of the function of the skeletal muscle and its power. Avoiding muscle fatigue pains is not easy since every exercise performed to train the muscles automatically creates muscle stress. The most important causes are muscle stress, inflammatory response to stress, excessive training load. Food is a great ally to obtain the desired results during training, and it also has an important function when it comes to muscle recovery. To make effort and fatigue even more effective, it is very important to combine sport with proper, healthy, natural, and balanced nutrition, and good supplementation that can assist exercise by making it more effective. Dietary strategies try to consider foods capable of acting on inflammation and the consequences of oxidative stress, physiological events that certainly appear in muscle fatigue, but which have their positive action on recovery and muscle adaptation to training. Natural supplements are products made from natural ingredients, often derived from plants or other biological sources, which are intended to supplement the diet and provide nutrients, vitamins, minerals, and other compounds beneficial to health. Thus, numerous phytochemicals and functional foods have been evaluated for their alleged ability to act and improve post exercise recovery, which represents the goal of the various nutritional strategies proposed to athletes, especially if they practice agonistic sports. Conversely, the trade-off between adaptation and recovery are infrequently considered. Therefore, many researchers are trying to understand whether prolonged administration of functional foods or / and supplements, which act on muscle fatigue, is a good strategy. This is a topic at the center of numerous studies that deal with the search for a correct diet for the athlete, which certainly requires a careful and meticulous analysis of the potential hormetic effect of prolonged use of such nutritional aids on the performance of athletes and therefore the effective acceleration of recovery from muscle fatigue.